Nearly Anhydrous Undissociated HF for the Removal of Hf / Ta / Zr Based Polymers after Plasma Etch, Selectively to Aluminum. (15th August 2017) - Cazes, Marine; Broussous, Lucile; Garnier, Philippe; Pizzetti, Christian; Gabette, Laurence; Besson, Pascal
Abstract : This paper investigates the possibility to fine tune a fluorinated solution to dissolve Ta, Zr, or Hf containing residues left after plasma etch, with maximum selectively towards silicon dioxide without corroding Aluminum. In this work amorphous "as dep" HfO2 has been assumed and proven to be a valuable test vehicle to evaluate the chemistry ability to dissolve such residues selectively towards other materials. In solvent/water mixtures, HF doesn't significantly hydrate until water content is predominant in the mixture. Plus, High proton concentration is key to reach a good aluminum protection and significant HfO2 dissolution rate in aqueous fluorinated solutions. By combining these properties an industrial solution has been engineered that achieves good dissolution of Ta, Zr, or Hf based polymers without corroding aluminum.